Pemberdayaan Budaya Kerja Efektif sebagai Kunci Keberhasilan Tim UKM Sakuntala - Rutinaias Haholongan; Bayu Pratama; Agustina Indriani; Nelli Novyarni; Hannissa Nurrahma; Taufik Hidayat; Silviana Hidayati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Empowering an effective work culture is the key to improving team performance to achieve the vision and mission of the Student Activity Unit (UKM), especially UKM Sakuntala. In improving the performance of the Sakuntala UKM team, they often face several challenges in terms of communication, motivation, training, performance monitoring and giving awards. To overcome these challenges, training was carried out using counseling and question and answer methods, presenting material on the concept of effective work culture in improving team performance. The research results show that an effective work culture, such as effective communication, teamwork, and motivation, has a significant impact on the performance of the Sakuntala UKM team. Material includes Empowering an Effective Work Culture, Collaboration and Teamwork, and the Role of Leaders. The results of this outreach show that all members of UKM Sakuntala have a fairly good understanding of effective work culture and understand enough about improving teamwork. This counseling also emphasizes the importance of harmonious relationships between leaders and subordinates, as well as a conducive work environment. It is hoped that this counseling can help Sakuntala UKM members develop a more effective work culture, improve communication skills, strengthen the performance of the Sakuntala UKM team, and provide insight into facing the challenges that exist in the organization. This provides a strong foundation for empowering a more effective work culture in the future for Sakuntala.